Organizing pneumonia in a carrier of human T-cell lymphotropic virus type-1 - Masahiro Yamasaki; Masaya Taniwaki; Kunihiko Funaishi; Noboru Hattori (Annals of Thoracic Medicine, 2020)
Human T-cell lymphotropic virus type-1 (HTLV-1)-associated bronchioloalveolar disorders (HABAs) are pulmonary disorders with various interstitial lung disease patterns that often occur in HTLV-1 carriers. Among HABAs, organizing pneumonia (OP) is extremely rare. We present a case of an 82-year-old woman with OP as a HABA. This patient responded to corticosteroid therapy; however, the patient required the continuation of oral corticosteroid therapy to avoid OP relapse. In cases of OP as a HABA that are not stabilized by treatment with corticosteroids, continuation of oral corticosteroid therapy might be considered.